The Impact of Technology on Accounting Education and Practice - Eka Merdekawati; Muhammad Nasrun; Andi Ferawati (Economics and Digital Business Review, 2024)
This study explores the impact of technological advancements such as automation, artificial intelligence (AI), and blockchain on accounting education and practice. A mixed-methods approach was used, integrating quantitative surveys and qualitative interviews with accounting educators, students, and professionals. The study examined how these technologies enhance accessibility, efficiency, and engagement in educational and professional settings. The findings indicate that automation significantly reduces time and errors in routine accounting tasks, allowing professionals to focus on strategic activities. AI improves audit quality and fraud detection through advanced data analysis, while blockchain ensures the integrity and transparency of financial transactions. Integrating data analytics and interactive tools in accounting education enhances student engagement and practical skills. However, challenges such as the digital divide and the need for continuous professional development and robust cybersecurity measures were identified. These results support the hypothesis that technological advancements positively impact accounting education and practice. The study underscores the necessity for educational institutions to incorporate advanced technological tools into their curricula and for accounting professionals to adapt to these innovations. Policymakers and educators must address the digital divide and provide ongoing professional development to maximize the benefits of technology. Future research should focus on longitudinal studies to track the evolving impact of these technologies and include diverse geographical and educational contexts.